BASLAWÍSH KLASs oqÍwshÍlarÍna Ses hám háriplerdi úyretiwde innovaciyalÍq jantasÍwdÍŃ Áhmiyeti - Paluaniyazova, S. (SCIENCE and SOCIETY, 2023)
This article discusses the stages of learning sounds and letters in primary mother tongue classes. In mother tongue lessons, students are pronounced to sounds and letters, and it is considered necessary to expand their correct writing skills.